Performance on Dengue Haemorrhagic Fever Prevention and Control of Village Health Volunteer in Thung Phraya Subdistrict, Sanam Chai Khet District, Chachoengsao Province: Performance on Dengue Haemorrhagic Fever Prevention and Control of Village Health Volunteer in Thung Phraya Subdistrict, Sanam Chai Khet District, Chachoengsao Province - Chaikwang, Suchitra; Sueprasertsith, Chakchai (RATANABUTH JOURNAL, 2026)
The research aimed to study: 1) the performance in dengue fever prevention and control of village health volunteers in Thung Phraya Subdistrict, Sanam Chai Khet District, Chachoengsao Province; and 2) factors affecting the performance in dengue fever prevention and control of village health volunteers in Thung Phraya Subdistrict, Sanam Chai Khet District, Chachoengsao Province. The sample used were 217 village health volunteers, with the sample size calculated using the G*Power program. Data was collected using a questionnaire with a reliability value between 0.832 – 0.937. In addition, the knowledge questionnaire regarding dengue fever yielded a KR-20 coefficient of 0.823, with item discrimination indicted ranging from 0.25 to 1.00. Data were analyzed using frequency distribution, percentage, mean, standard deviation, and multiple regression analysis. The research results found that: 1) the performance of dengue haemorrhagic fever prevention and control of village health volunteers in Tung Phraya Subdistrict, Sanam Chai Khet District, Chachoengsao Province was overall at a high level. When considering each aspect, it was found that the aspect of participation of local administrative organizations and communities was at a high level with the highest mean, followed by the aspect of disease control operations, the aspect of surveillance, and the aspect of coordination with l organizations at a high level, and the last rank was the aspect of public relations at a high level, respectively. 2) the factors affecting the performance of dengue haemorrhagic fever prevention and control of village health volunteers in Tung Phraya Subdistrict, Sanam Chai Khet District, Chachoengsao Province, found that the highest level of education and organizational support (in terms of personnel, materials and equipment, and management) affected the performance in dengue fever prevention and control of village health volunteers in Thung Phraya Subdistrict, Sanam Chai Khet District, Chachoengsao Province, with statistical significance at levels 0.05, 0.05, 0.01, and 0.05, respectively.